Computational wind engineering: 30 years of research progress in building structures and environment. Issue 234 (March 2023) - Potsis, Theodore; Tominaga, Yoshihide; Stathopoulos, Ted
Abstract: The paper reviews the evolution of computational wind engineering from environmental and structural perspectives, since the inaugural conference of computational wind engineering held in Tokyo 30 years ago (CWE 92). The progress in computational methodologies and important aspects for accurate analysis are discussed. As a groundwork for the application of computational fluid dynamics (CFD) to various environmental issues, the importance of accurate modeling of atmospheric boundary layer, urban boundary layer, and urban canopy layer is pronounced. Environmental applications refer to urban micro-climate, pedestrian level wind, near-field pollutant dispersion, natural and urban ventilation, urban wind energy and snow/sand erosion and accumulation. Structural applications refer to wind loading on low- and high-rise buildings, including wind directionality. The most seminal contributions are examined, and their results are presented. It becomes clear that the engineering community has gained more benefits from environmental than structural computational wind engineering applications, mainly due to the usually less demanding computational needs for the former. Future challenges in CFD applications are thoroughly discussed and the need to bridge the gap between environmental and structural applications is highlighted. Highlights: Computational wind engineering progress since the seminal conference of CWE 1992, in environmental and structural applications. Turbulence models, verification, validation, and best practice guidelines in computational wind engineering. Progress is environmental research field of pedestrian level wind, near-field pollutant dispersion, natural ventilation, urban ventilation, urban wind energy, snow/sand erosion and accumulation. Progress in structural research field for design of low- and high-rise buildings. Future perspective of CFD application to environmental and structural problems.